2023
DOI: 10.1007/s11274-023-03548-w
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of pyocyanin - why and how to steer its production?

Abstract: The ambiguous nature of pyocyanin was noted quite early after its discovery. This substance is a recognized Pseudomonas aeruginosa virulence factor that causes problems in cystic fibrosis, wound healing, and microbiologically induced corrosion. However, it can also be a potent chemical with potential use in a wide variety of technologies and applications, e.g. green energy production in microbial fuel cells, biocontrol in agriculture, therapy in medicine, or environmental protection. In this mini-review, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…The presence of organic solvents like toluene and chloroform as well as surfactants such as Triton X-100 and Tween 20 has also been experimentally proven to enhance pyocyanin synthesis (Ozdal 2019 ). However, certain compounds including nitric oxide, nanomaterials like silver nanoparticles (Ag NPs) and zinc oxide nanoparticles (ZnO NPs), phenolic compounds such as quercetin and ellagic acid, sodium citrate, benzimidazolium salts, and antimicrobial peptides like calgranulin C have been shown to inhibit the synthesis of pyocyanin, possible by interfering with the expression of phzM (Zhou et al 2022 ; Jabłońska et al 2023 ).…”
Section: Production Of Pyocyaninmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of organic solvents like toluene and chloroform as well as surfactants such as Triton X-100 and Tween 20 has also been experimentally proven to enhance pyocyanin synthesis (Ozdal 2019 ). However, certain compounds including nitric oxide, nanomaterials like silver nanoparticles (Ag NPs) and zinc oxide nanoparticles (ZnO NPs), phenolic compounds such as quercetin and ellagic acid, sodium citrate, benzimidazolium salts, and antimicrobial peptides like calgranulin C have been shown to inhibit the synthesis of pyocyanin, possible by interfering with the expression of phzM (Zhou et al 2022 ; Jabłońska et al 2023 ).…”
Section: Production Of Pyocyaninmentioning
confidence: 99%
“…Though pyocyanin is associated with several medically beneficial properties, it is also actively involved in several biomedical challenges posed by Pseudomonas aeruginosa (Jabłońska et al 2023 ). Pyocyanin’s ability to interfere with cellular functions in normal human cells exacerbates the effects of P. aeruginosa infections, especially in immunocompromised individuals, hospital patients, victims of burn wounds and other skin injuries, as well as those suffering from cystic fibrosis (CF).…”
Section: Biomedical Challenges Due To Pyocyaninmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] In view of the importance of pyocyanin in the pathogenicity of P. aeruginosa, the inactivation/deactivation of the molecule or the modulation of pyocyanin production was proposed as an alternative approach to disarming the pathogen. 9,10 Indeed, the inactivation of virulence factors (including pyocyanin) by adsorption has been shown to attenuate the cytotoxicity of the pathogen by neutralizing virulence factors, and transcriptionally suppress virulence gene expression. 11,12 Our earlier study showed that clay minerals (Namontmorillonite and sepiolite) adsorbed pyocyanin and probably transformed pyocyanin in the interlayer of the montmorillonite and in the tunnel of sepiolite.…”
Section: Introductionmentioning
confidence: 99%